НВП «Електрон-Карат» — 45 років успіху - Vakiv, M. M.; Syvorotka, I. M.; Bulat, A. M. (PE "Politekhperiodika", Book and Journal Publishers, 2017)
The paper is devoted to the Scientific-Production Company «Electron-Karat», its history from the moment of creation to the present day. Described are the significant stages of the company’s development and the scientific and technical results achieved by its team during 45 years.